Analysis of the results of treatment of patients with malignant tumors of the salivary glands - V. T. Vayradyan; A. M. Mudunov; V. D. Ermilova; R. I. Azizyan; I. A. Zaderenko; S. B. Aliyeva; E. L. Dronova (Опухоли головы и шеи)
Objective: improve results of the treatment of patients with malignant salivary gland neoplasm (MSGN).Materials and methods. Analysis of 417 patients suffering from MSGN treated in the Federal State Budgetary Institution “N.N. Blokhin Russian Cancer Research Center” from 1988 to 2014. All the subjects were divided into 4 main groups according to the treatment assigned: group of the surgical treatment – 27.3 % (n = 114), group of the combined treatment (surgery and radiotherapy (RT)) – 54.0 % (n = 225), group of the complex treatment (surgery, radiotherapy and chemotherapy) – 10.5 % (n = 44), group of conservative treatment (radiotherapy and/or chemotherapy) – 8.2 % (n = 34).Results. Best 5-year disease-free survival (DFS) was observed in patients with localization of the tumor process in the minor salivary glands (MSG), mucosal tunic (MT) of mouth (73.2 ± 5.5%) and parotid gland (62.3 ± 3.3 %), while the lowest survival rate was observed in tumors of sublingual salivary gland (0%) (median was not achieved, p = 0.07). Depending on the morphological variants the best 5-year DFS was observed in groups of myoepithelial carcinoma, and acinar cell carcinoma: 81.3 ± 9.8 and 79.1 ± 8.4 %, respectively (median was not reached, p > 0.05); the worst survival rate was observed in patients with squamous cell carcinoma, carcinoma of the salivary ducts and adenocarcinoma: 45.7 ± 15.5; 50.3 ± 12.7 and 53.0 ± 5.5 %, respectively (median was not reached). In poorly differentiated tumors (G3 ) 5-year DFS was lowest and was equal to 32.7 ± 4.1 %, while in G1 tumors – 83.6 ± 3.1% (p = 0.000001). In G3 tumors addition of radiotherapy to the surgery significantly reduces the incidence of local recurrence - from 51.4 % (surgical treatment alone) down to 33.8 % (combined treatment) (p = 0.08). There was a significant decrease in 5-year disease-free survival rate from 74.2 ± 2.6 % without any adverse pathological signs down to 37.9 ± 5.4% in the presence of these signs (p = 0.000001). Cervical lymph node dissection is absolutely indicated for tumor localization in submandibular salivary gland, as it reduces an incidence of local recurrence: 15.8 % versus 25.9 % in the group without lymph node dissection, p> 0.05. In case of other MSGN localizations, prophylactic lymphadenectomy does not improve long-term outcomes. Radiotherapy in the post-op period significantly improves long-term results of treatment in comparison with a group of preoperative radiotherapy (local recurrence rates are 29.5 and 9.7 %, respectively, p = 0.0002). The use of chemotherapy can be justified in case of neoplasms with poor differentiation (G3 ) since this significantly reduces an incidence of distant metastases (17.6 and 9.1 % in groups of the combined treatment and in the group of conservative chemoradiotherapy respectively, p > 0.05).